The psychology of the impulsive-reflective cognitive style And its relationship to patience among a sample of students of the faculties of education at the Universities of Baghdad and Al-Mustansiriya (Journal of the College of Basic Education, 2022)
Patience is one of the most prominent manifestations of Quranic morals that the Holy Qur’an came with, and it is one of the most moral concepts mentioned in the Holy Qur’an, as Imam Al-Ghazali said in the book of patience and gratitude that God mentioned patience in the Holy Qur’an seventy times, and the Almighty said in His Holy Book ((And He rewarded them for what they were patient with). Paradise and silk)) “Man 12”, and patience is of great importance in human life, especially in our current era full of contradictions, troubles, wars, international occupations, and psychological, economic and social crises. All of this requires patience and adaptation. And the patient have a great status with God, as the Almighty said ((And give glad tidings to the patient))